(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article examines the main philosophical and ethical thoughts of Yusuf Balasaguni, which played a significant role in the development of the philosophical thought of the medieval Turkic peoples, in particular the Kyrgyz. It is noted that Yusuf Balasaguni’s poem “Kutadgu bilig” is primarily an ethical and didactic work. Therefore, it deals with ethical issues in the most detail. Their features lie in the fact that the basic concepts of morality are personified in the images of the main characters of the poem.